Severity Levels of Disability Among Older Adults in Low- and Middle-Income Countries: Results From the Study on Global Ageing and Adult Health (SAGE) - Salinas-Rodríguez, Aarón; Rivera-Almaraz, Ana; Scott, Ashley; Manrique-Espinoza, Betty (Frontiers in Medicine, 2020)
Background. Recent studies suggest the importance of distinguishing the severity levels of disability in the older adult (OA) population. However, there is still no consensus regarding an optimal classification. Few studies have estimated the prevalence of severe disability, and the results have been confined to high-income countries. There is no evidence for low- and middle-income countries. Therefore, the aim of this study was to provide estimates of the levels of severity associated with disability in OA populations in low and middle-income countries and to examine their relationship with health and socioeconomic factors. Methods. We used data from the Study on Global Ageing and Adult Health (SAGE), wave 1 (2007–2010). Nationally representative samples of adults over 50 years from China, Ghana, India, Mexico, Russian Federation and South Africa were analyzed (n=33,641). We measured disability using the WHO Disability Assessment Instrument version 2.0 (WHODAS 2.0). Disability levels according to severity were identified through the use of latent class analysis. Socioeconomic and health factors associated with severe disability were estimated using ordinal logistic regression models. Results. We identified four groups of OA: (1) without disability, 43.4% (2) mild disability, 33.3% (3) moderate disability, 15.3%, (4) severe disability, 8.0%. These results were heterogeneous for the six countries analyzed. Education and socioeconomic status were significantly associated with severe disability along with the following chronic conditions: angina, arthritis, asthma, cataracts, chronic obstructive pulmonary disease, depression, diabetes, and stroke. Severe disability was also associated with the frailty status, sarcopenia and mild cognitive impairment. Conclusions. In this study, we estimated severity levels of disability for the OA population in low- and middle-income countries. Our results show that severe disability affects 8% of OA, and that there are important socioeconomic and health factors associated with this condition. Measuring the severity of disability is a critical element to study the causes and consequences of aging. Moreover, the identification of OA with severe disability is vital to design prevention programs, modify interventions or develop enabling environments.